Public Organization Performance Evaluation Using the Balanced Scorecard - Muhammad Taufiq; Giska Nur Aziza (Relasi : Jurnal Ekonomi, 2024)
Performance measurement evaluation is essential for driving continuous improvement in public sector organizations. This study addresses recurring issues at the Bandung City Regional Revenue Agency (UPT PPD Central Bandung Region), which has experienced a continuous decline in PBB tax realization alongside a shortage of human resources. If left unaddressed, these issues will permanently degrade public service quality. To evaluate performance comprehensively, this study implements the Balanced Scorecard (BSC) method by analyzing Key Performance Indicators across both financial and non-financial dimensions. The research adopts a descriptive quantitative approach, utilizing both primary and secondary data sources. The results indicate that the overall performance of the UPT PPD Central Bandung Region using the BSC framework is in good standing, achieving a total score of 85.42%, which places the organization in the green level category. In detail, the customer perspective achieved the highest performance value at 30.44%, reflecting high taxpayer satisfaction. This is followed by the financial perspective at 22.43%. Furthermore, the internal business process perspective scored 12.79%, showcasing effective innovations that accelerate service delivery. Finally, the learning and growth perspective scored 19.74%, indicated by high employee satisfaction and strong expertise in their fields. This balanced scorecard evaluation confirms that despite structural challenges, the agency maintains a highly commendable quality of service.